The hostile hospital - Snicket, Lemony; Helquist, Brett (New York : HarperCollins Publishers, 2001)
On the run after being falsely accused of murder, the three Baudelaire orphans find themselves in the Heimlich Hospital, with the evil Count Olaf in close pursuit.
Keywords: Orphans -- Juvenile fiction; Siblings -- Juvenile fiction; Hospitals -- Juvenile fiction